2008
DOI: 10.1063/1.2967468
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopic study of Ge2Sb2Te5 etched by fluorocarbon inductively coupled plasmas

Abstract: X-ray photoelectron spectroscopy was used to determine the level of surface fluorination damage of Ge2Sb2Te5 (GST) etched by fluorocarbon gases at different F/C ratios. When blank GST was etched, the gas with a higher F/C ratio produced a thinner C–F polymer on the etched surface but fluorinated Ge, Sb, and Te compounds were observed in the remaining GST. When the sidewall of the etched GST features was investigated, a thicker fluorinated layer was observed on the GST sidewall etched by the higher F/C ratio ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…What's more, two smaller additional peaks are presented in both Sb 3d and Te 3d spectra, which can be attributed to Sb-F x (the peaks at 530.67 eV and 540.0 eV in Sb 3d spectra) and Te-F x (the peaks at 576.57 eV and 587.04 eV in Te 3d spectra), respectively. 22 With the increasing time of Ar ion sputtering, the two small peaks in both Sb 3d and Te 3d spectra are gradually undetected, while the Sb 3d and Te 3d peaks slowly appear. From Fig.…”
Section: Resultsmentioning
confidence: 95%
“…What's more, two smaller additional peaks are presented in both Sb 3d and Te 3d spectra, which can be attributed to Sb-F x (the peaks at 530.67 eV and 540.0 eV in Sb 3d spectra) and Te-F x (the peaks at 576.57 eV and 587.04 eV in Te 3d spectra), respectively. 22 With the increasing time of Ar ion sputtering, the two small peaks in both Sb 3d and Te 3d spectra are gradually undetected, while the Sb 3d and Te 3d peaks slowly appear. From Fig.…”
Section: Resultsmentioning
confidence: 95%
“…5) We demonstrated that less damaged etching can be performed with a lower F/C ratio fluorocarbon gas owing to the thicker C-F polymer formed on the GST surface and sidewalls during the etching, which protects against the diffusion of fluorine radicals to the GST film. In this article, the etching of GST with three types of halogen gas is described and the extent of the surface damage of GST during the etching by different halogen-gas-based inductively coupled plasmas (ICPs) such as CF 4 , Cl 2 , and HBr is investigated.…”
Section: Introductionmentioning
confidence: 90%
“…The 100-nm-thick GST samples were prepared on SiO 2 /Si substrates by rf magnetron co-sputtering from GeTe and Sb 2 Te 3 targets and some of the samples were patterned with an SiO 2 hard mask after depositing a Ti (as an adhesion layer of 5 nm)/ TiN layer on the GST films similarly to those described in our previous article. 5) The composition of the sputterdeposited GST was known to be Ge : Sb : Te ¼ 22 : 22 : 56 (XPS analysis showed that the actual composition was Ge : Sb : Te ¼ 26 : 26 : 48). The etch depth was measured using a surface profilometer (Tencor Alpha-step 500).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…18 Many studies on the etching of GST materials and their damage characteristics can be found in previous studies. [19][20][21][22][23][24] However, the etch characteristics OTS materials including the damages by the etching using halogen gas-based plasmas have not been reported yet, and it is very important to understand the effect of the halogen etch gases for low-damage OTS etching.…”
mentioning
confidence: 99%